A new PAPR reduction in OFDM-WLAN systems by hybrid algorithm of PTS and APPR methods - Pradabpet, C.; Yoshizawa, S.; Miyanaga, Y.; Dejhan, K. (My University, 2007)
In this paper, we propose a new PAPR reduction technique by a hybrid algorithm based on a partial transmit sequence (PTS) and adaptive peak power reduction (APPR) methods. This technique is used in a system based on Orthogonal Frequency Division Multiplexing (OFDM). OFDM has many orthogonally modulated subcarriers which unexpectedly give a large peak to average power ratio (PAPR) and tends to reduce the power efficiency of a RF amplifier. A sequence of input data is rearranged by PTS for the reduction of PAPR and then fed to APPR process in the proposed system. The APPR method controls the peak level of the modulation signal by an adaptive algorithm. It reduces modulation signals over a predefined range. A proposed reduction method consists of these two methods and realizes both advantages at the same time. In simulation results, the proposed method shows the improvement on PAPR and also the high performance on bit error rate performance of an OFDM system. ©2007 IEEE.
Keywords: Adaptive Peak Power Reduction (APPR); OFDM; PAPR; PTS; WLAN